1986
DOI: 10.1159/000167338
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Right Dose for Beta-Blocker Treatment of Hypertension: Experience with Tertatolol

Abstract: The determination of the optimum dosage for antihypertensive therapy, i.e. the unit dose and the administration frequency, remains one of the least discussed subjects. For β-blockers as well as for other drugs, this determination is mainly based on the dose-effectiveness curve, the top of which corresponds to the right dose. Thus, a wide range of doses should be tested, and this as early as possible during drug development. The first step is to assess the optimum β-blocking dose in healthy volunteers during ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…As also shown in other papers on this issue [4][5][6], the average therapeutic dose of tertatolol is 5 nig, given as a single daily administration. However, it is important that the activity and acceptability of any molecule under development be compared not only with those of pla cebo but also, if possible, with those of other agents from the same therapeutic class.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As also shown in other papers on this issue [4][5][6], the average therapeutic dose of tertatolol is 5 nig, given as a single daily administration. However, it is important that the activity and acceptability of any molecule under development be compared not only with those of pla cebo but also, if possible, with those of other agents from the same therapeutic class.…”
Section: Discussionsupporting
confidence: 62%
“…In man, the dose of 5 mg once daily has been shown to exert an efficient antihypertensive effect all over the 24 h [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…ß-blockers, introduced in 1964 by Prichard, are presently the most frequently used antihypertensive drugs because of their efficacy, good acceptability and simplicity of administration [3,4], In recent short-term studies [5][6][7], tertatolol, a new potent ß-blocking drug, was shown to be efficient and well accepted at the dose of 5 mg orally once daily. It was nevertheless necessary, since hypertension needs a long term therapy, to appraise its effects on a large range of patients and over a long period of time.…”
Section: Introductionmentioning
confidence: 99%